La psicología en Colombia - Ardila, Rubén (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
This article discusses the historical development of psychology as a science and a profession in Colombia, with emphasis on the social factors that accompanied its development. The preparation and training of university students of psychology is analyzed and their limitation and possibilities discussed. The principal areas of work in psychology in this country are enumerated, and the percentages of professionals in each area are given. The functions of the "Federación Colombiana de Psicología,” the principal psychological association, are explained, as in the orientation of the Revista de Psicología, the only specialized publication in this science. This overall view of Colombian psychology helps to show the existing gaps and to plan the development of the profession. Similar studies in other Latin American countries would be extremely useful.